Estudo de algumas reações oxoacidobásicas no solvente NaCl fundido entre 1100K e 1200K - Koeller Sérgio Luiz; Combes Richard Louis (Química Nova, 2002)
Equilibrium constants (K) of some oxoacidbasic reactions in molten NaCl in the temperature range of 1100K to 1200K, have been measured potentiometrically with a calcia stabilized zirconia oxide ion (O2-) indicator electrode. In molten NaCl at 1100K the pKs values (in molality scale) for HCl/H2O and HO-/H2O are respectively 11.0 ± 0.3; 1.6 ± 0.3 and the pKs for CaO is 4.3 ± 0.3. The results have been compared with those determined previously by Combes for the molten equimolar NaCl-KCl mixture and are in good agreement with literature data and gives some qualitative explanation of the comparison of oxoacidbasic properties between molten NaCl and NaCl-KCl.